ONLINE LEARNING FOR ENGLISH LANGUAGE TEACHING - Sari, Ima Frafika (LP. Ma'arif Janggan Magetan, 2020)
This research elaborated the definition of Online Learning and the online learning application in English Language Teaching. The methodology of research uses qualitative research in explaining the Online Learning Application for English Language Teaching. This research is still lacking research in online learning for English Language Teaching; therefore, it significant to be done. The finding of the research is followed: First, online learning is the worldwide technologies that use the web, e-mail, new groups and texts, audio, and video conferencing. Online learning is always connected to the internet. It can use for long-distance or not in one place. The students can use in certain conditions “distance learning”. Second, Online learning supported the proper application in English Language Learning, such as: Edmodo, Zoom, Blogs, WhatsApp Group, Email, SeeSaw, Sway, Google Classroom, ClassDojo, Show My homework, Surveymonkey in-app surveys, SmartSurvey. Penelitian ini menjelaskan mengenai pembelajaran online (via Internet) dan pembelajaran online untuk mata kuliah bahasa Inggris. Metode yang dunakan adalah penelitian kualitatif untuk menjelaskan pembelajaran online (Aplikasi via Internet) untuk pembeljaran bahasa Inggris. Penilitian ini masih sedikit dilakukan, oleh karena itu tetap dilakukan. Pembahasan dari permasalahan penelitian ini adalah: Pertama, pembelajaran online merupakan teknologi yang digunakan oleh seluruh dunia yang menggunakan web, email, grup dan teks baru, konferensi audio dan video. Pembelajaran online selalu terhubung di internet. Pemebeljaran inidapat dilakukan dalam jarak jauh atau tidak di satu tempat. Siswa dapat menggunakan “pembelajaran jarak jauh” dalam kondisi tertentu. Kedua, pembelajaran online ini didukung dengan aplikasi yang mudah dalam pembelajaran Bahasa Inggris, seperti: Edmodo, Zoom, Blogs, WhatsApp Group, Email, SeeSaw, Sway, Google Classroom, ClassDojo, Show My homework, Surveymonkey in-app surveys, SmartSurvey.